If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -1a = 2a + -6 Reorder the terms: 11 + -1a = -6 + 2a Solving 11 + -1a = -6 + 2a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2a' to each side of the equation. 11 + -1a + -2a = -6 + 2a + -2a Combine like terms: -1a + -2a = -3a 11 + -3a = -6 + 2a + -2a Combine like terms: 2a + -2a = 0 11 + -3a = -6 + 0 11 + -3a = -6 Add '-11' to each side of the equation. 11 + -11 + -3a = -6 + -11 Combine like terms: 11 + -11 = 0 0 + -3a = -6 + -11 -3a = -6 + -11 Combine like terms: -6 + -11 = -17 -3a = -17 Divide each side by '-3'. a = 5.666666667 Simplifying a = 5.666666667
| Y-5=4(x-1) | | -1.8(1.03n+0.9)=2.2(2.58n+1.4)-1.4 | | 4.75=a+1.85 | | 1.30m=6.50 | | 6.50=m-1.30 | | 6.50=M+1.30 | | 2a+b=24 | | 2a+3b-a+4a= | | y=65x | | 3a+5a+a= | | (x^4+y^2)dx-(xy)dy=0 | | 14-(6-3r)=4r-r | | y=6y-8y | | 6x-3=x+7 | | 2m+15=8 | | W(a)=2afindw(3) | | H(a)=a^3findh(2) | | -3+2v-1+4=v-3 | | -4n+3n=-15+n+4+5 | | 4p+25=(6-3)-3(4-3p) | | -12-3m=4m-5m | | 7a-11=-3+6a | | -4+-22=-7x+14 | | 12+3n=3n-6n | | -10+6+4h+3h=6h-4+3 | | 300x^2-120x-8=0 | | W(a)=2a | | H(a)=a^3 | | 100x^3-60x^2-8x=0 | | 4p-7=5p+9 | | 2p+3q=28 | | 7v+10=7v+20 |